A polymeric immunoglobulin—antigen fusion protein strategy for enhancing vaccine immunogenicity. Issue 12 (21st July 2018) - Webster, Gina R.; van Dolleweerd, Craig; Guerra, Thais; Stelter, Szymon; Hofmann, Sven; Kim, Mi‐Young; Teh, Audrey Y‐H.; Diogo, Gil Reynolds; Copland, Alastair; Paul, Mathew J.; Hart, Peter; Reljic, Rajko; et al.
Summary: In this study, a strategy based on polymeric immunoglobulin G scaffolds (PIGS) was used to produce a vaccine candidate for Mycobacterium tuberculosis . A genetic fusion construct comprising genes encoding the mycobacterial Ag85B antigen, an immunoglobulin γ‐chain fragment and the tailpiece from immunoglobulin μ chain was engineered. Expression was attempted in Chinese Hamster Ovary (CHO) cells and in Nicotiana benthamiana . The recombinant protein assembled into polymeric structures (TB‐PIGS) in N. benthamiana, similar in size to polymeric IgM. These complexes were subsequently shown to bind to the complement protein C1q and FcγRs with increased affinity. Modification of the N‐glycans linked to TB‐PIGS by removal of xylose and fucose residues that are normally found in plant glycosylated proteins also resulted in increased affinity for low‐affinity FcγRs. Immunization studies in mice indicated that TB‐PIGS are highly immunogenic with and without adjuvant. However, they did not improve protective efficacy in mice against challenge with M. tuberculosis compared to conventional vaccination with BCG, suggesting that additional or alternative antigens may be needed to protect against this disease. Nevertheless, these results establish a novel platform for producing polymeric antigen‐IgG γ‐chain molecules with inherent functional characteristics that are desirable in vaccines.